Upper limb ischemia in a newborn following difficult delivery - Drkamal alzoghby; Drmedhat elsayed; DrOthman alamoudi; Drahmed Rezan (Elsevier, 2020)
Neonatal limb ischemia is a very rare condition. The lower limb ischemia is more common than upper limb ischemia in incidence. The limb ischemia in such an age group urges for top urgent proper management. Although the neonates are vulnerable to limb ischemia, there are no clear guidelines of management in the literature. Only case reports and single personal experiences are available for the management of such critical conditions.Our aim:To present a unique case of acute right upper ischemia at birth and to demonstrate a successful acceptable protocol or plan of management which end with limb salvage.